1985
DOI: 10.1002/j.1460-2075.1985.tb03903.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of calf thymus type II DNA topoisomerase by poly(ADP-ribosylation).

Abstract: The effect of poly(ADP‐ribosylation) on calf thymus topoisomerase type II reactions has been investigated. Unknotting of phage P4 head DNA, and relaxation and catenation of supercoiled PM2 DNA are inhibited. We conclude that the inhibition results from poly(ADP‐ribosylation) on the following grounds. Firstly, the enzyme poly(ADP‐ribose) (PADPR) synthetase and NAD are required, secondly, the competitive synthetase inhibitor nicotinamide abolishes topoisomerase inhibition, and thirdly, the polymer alone is not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(38 citation statements)
references
References 35 publications
(19 reference statements)
1
37
0
Order By: Relevance
“…The apparent molecular masses of some of the poly(ADPribose) -nonhistone conjugates matched the molecular sizes of nuclear enzymes and other proteins that have previously been shown to function as acceptors for poly(ADP-ribose) in vitro: poly(ADP-ribose) synthase (1 10 kDa) [47 - (172 kDa) [30] as well as actin (43 kDa) [50]. The presence Fig.…”
Section: Identification Ofpoly(adp-ribose) Synthase and D N A Topoisomentioning
confidence: 54%
See 1 more Smart Citation
“…The apparent molecular masses of some of the poly(ADPribose) -nonhistone conjugates matched the molecular sizes of nuclear enzymes and other proteins that have previously been shown to function as acceptors for poly(ADP-ribose) in vitro: poly(ADP-ribose) synthase (1 10 kDa) [47 - (172 kDa) [30] as well as actin (43 kDa) [50]. The presence Fig.…”
Section: Identification Ofpoly(adp-ribose) Synthase and D N A Topoisomentioning
confidence: 54%
“…A frequent explanation is that poly(ADP-ribose) may regulate cellular events by directy modulating the enzymic activities of the modified proteins [5] in analogy to the action of extranuclear mono(ADP-ribosyl) transferases [3]. This view relies on the observation that poly(ADP-ribosy1)ation inhibits the activities of many nuclear enzymes in vitro: Ca2+/Mg2-dependent endonuclease [25], DNA ligases I and I1 [26,271, DNA topoisomerase I [28, 291 and 11 [30], DNA polymerase a and b [26], RNA polymerase I [32] and I1 [33], terminal deoxynucleotidyltransferase [26], ribonucleases [34] and poly(ADP-ribose) synthase itself [35]. An alternative model is based on the capacity of the poly(ADP-ribose) synthase to accumulate large amounts of negatively charged and possibly branched polymer chains at the site of the DNA break [36,371.…”
mentioning
confidence: 99%
“…their activity (Ferro and Olivera, 1984;Darby et al, 1985). Consistent with these observations Mattern et al (1987) demonstrated potentiation of camptothecin and teniposide cytotoxicity by the PARP inhibitor, 3-aminobenzamide (3AB), in L1210 cells.…”
mentioning
confidence: 67%
“…Thus, poly(ADP) ribosylation decreases enzyme activity [50], whereas phosphorylation enhances catalytic-DNA turnover in vitru [51, 521. In eukaryotic cells, phosphorylation of topoisomerase I1 by a casein-kinase-11-like protein kinase is involved in controlling processes of cellular growth and the cell cycle [53,541.…”
Section: Discussionmentioning
confidence: 99%